Legal Certainty For Investment-Based on Insurance Policy Holders (UNITLINKS) After The Establishment of Alternative Institutions For Financial Services Dispute Settlement (LAPS SJK) - Wetria Fauzi; Zulkifli (Master of Law Program, Ekasakti University, 2024)
Legal certainty is a justifiable protection against arbitrary actions which means that someone will be able to get something that is expected under certain circumstances. The problem is How is the legal certainty of unitlink dispute resolution after the establishment of Alternative Dispute Resolution Agency in the Financial Service Sector (LAPS SJK). The method in writing is by using a normative juridical approach. Legal certainty related to institutional certainty has been represented by the existence of this LAPS SJK. LAPS SJK which is an integrated dispute resolution with this dispute resolution will be faster because it has been centralized considering the increasing number of hybrid financial products. The legal basis for the LAPS SJK is regulated in POJK Number 61/POJK.07/2020 concerning Alternative Institutions for Settlement of Financial Services Sector Disputes. The urgency of the LAPS SJK is needed because of the current condition of the financial services industry, financial services and products that are hybrid or integrated with each financial service sector. The existence of the LAPS SJK provides legal certainty in the dispute resolution mechanism. The principles of this institution are independent, fair, effective and efficient and easily accessible.Policyholders should agree with insurance companies to use LAPS SJK in resolving unitlink insurance disputes, because this forum will provide legal certainty by providing fair and objective solutions. OJK and LAPS SJK further socialize the existence of LAPS SJK. As far as possible for dispute resolution when it cannot be reached internally with the insurance company, the parties choose LAPS SJK by ringing the clause in the unitlink insurance policy.